Breeding objectives for Red Maasai and Dorper sheep in Kenya—A participatory approach - Zonabend König, Emelie; Mirkena, T.; Audho, James O.; Ojango, Julie M.K.; Strandberg, E.; Näsholm, A.; Malmfors, B.; Okeyo Mwai, Ally; Philipsson, J. (American Society of Animal Science, 2014)
The Red Maasai sheep breed is under threat due to indiscriminate crossbreeding and strategies are needed to conserve and improve the breed. The aim of this study was to understand farmers’ preferences for important traits of flocks of Red Maasai, Dorper and crosses in two different areas, Amboseli and Isinya, in Kenya. Farmers identified three ewes that represented the best, average, and poorest within its breed group of each farm and gave reasons for their ranking. The most important traits were body size and growth rate and thereafter milk yield. The Red Maasai was preferred for its better reproduction and tolerance against diseases and drought. In the harshest area, Amboseli, all breed groups had about the same body weight, whereas in Isinya, where conditions are better and farmers are more market oriented, Dorper and crosses had superior weights.